Pengaruh Penggunaan Media Permainan Ludo Terhadap Hasil Belajar Peserta Didik Materi Animalia Kelas X SMAN 8 Luwu Timur - Arvia Larasati; Muh. Rapi; Dahlia Patiung (Al-AHYA: Jurnal Pendidikan Biologi, 2022)
The use of media in learning is very important to improve student learning outcomes. One of the widely used media is game media. This research is a quasi experiment with a non-equivalent control group design. The research objective was to determine the effect of ludo game media on the learning outcomes of class X students of SMAN 8 Luwu Timur. The research was conducted in two classes, X IPA 3 as the experimental class and X IPA 2 as the control class with 18 students each. The research sample was selected by purposive sampling technique. Data was collected through a multiple-choice test with 25 multiple-choice questions. The results of the study were analyzed descriptively and inferentially using the t test. The results showed that the average learning result of the experimental class was 83.11, much higher than that of the control class, which was 60.00. The significance value of the t test shows a value of 0.000 <0.05 (sig @). So it can be concluded that the application of ludo game media has an effect on student learning outcomes in animalia material for class X IPA SMAN 8 Luwu Timur.